2008
DOI: 10.1016/j.cellimm.2007.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Opioid and nociceptin receptors regulate cytokine and cytokine receptor expression

Abstract: Opioids were originally discovered because of their ability to induce analgesia, but further investigation has shown that the opioids regulate the function of cells involved in the immune response. We suggest that the regulation of cytokine, chemokine, and cytokine receptor expression is a critical component of the immunomodulatory activity of the opioids. In this paper we review the literature dealing with the regulation of cytokine and cytokine receptor expression by agonists for the three major opioid recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 87 publications
3
77
1
1
Order By: Relevance
“…Opioids regulate the expression of inflammatory cytokines and their receptors, and immune cells under the influence of cytokines can release endogenous opioids at sites of inflammation [33,55,56]. It has [21] been suggested that the κ-and μ-opioid receptors play opposing roles, with the κ-opioid receptor activation inducing an anti-inflammatory response while the μ-opioid receptor favors a pro-inflammatory response [57]. However, the picture is far more complex.…”
Section: Opioids and Inflammation Are Closely Interrelatedmentioning
confidence: 99%
“…Opioids regulate the expression of inflammatory cytokines and their receptors, and immune cells under the influence of cytokines can release endogenous opioids at sites of inflammation [33,55,56]. It has [21] been suggested that the κ-and μ-opioid receptors play opposing roles, with the κ-opioid receptor activation inducing an anti-inflammatory response while the μ-opioid receptor favors a pro-inflammatory response [57]. However, the picture is far more complex.…”
Section: Opioids and Inflammation Are Closely Interrelatedmentioning
confidence: 99%
“…1a,b), indicating that the absence of opioid receptors does not markedly alter T lymphocytes proliferative capabilities under these conditions. Exposure to opiates has been shown previously to alter TH cytokine profiles (Finley et al 2008). Here, we investigated whether global opioid receptor deletion would impact on TH1/TH2 cytokines by analysing IL-2 and IFNγ TH1 and IL-4 TH2 cytokines in supernatants by ELISA under the same T lymphocyte stimulatory conditions than for proliferation.…”
Section: Proliferation and Cytokine Responsesmentioning
confidence: 95%
“…Equally, the practice is also reported to cause a dysregulation in cytokine production [87,88]. For instance, levels of circulating Acrp30 are revealed to be markedly reduced in frequently injecting heroin addicts [23,24].…”
Section: Illicit Substance Use and Adiponectin Productionmentioning
confidence: 99%